Nutritional Content Analysis of Crop Residues in Three Agroecologies in East Gojjam Zone - Alemu Gashe Desta (The Scientific World Journal)
Livestock is important and plentiful in Ethiopia, but its potential is not being used to its full extent due to limited supply and inconsistent feed supply. This has a negative impact on livestock productivity in the tropics, where crop residues are used as livestock feed. The analysis of the nutritional content of feed and the measurement of feed production are crucial for maintaining the optimal balance of annual livestock feed and improving livestock production. However, no research has been conducted on the nutritional composition of the crop residues in the East Gojjam zone. Therefore, this study was conducted to analyze the nutritional content of crop residues in the three agroecologies in Ethiopia’s East Gojjam zone. Ash, dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) were analyzed in the feed samples. According to the findings, the overall mean content of DM, ash, OM, CP, NDF, ADF, and ADL was 92.3, 5.2, 87.1, 4.1, 71, 56.6, and 9.6%, respectively. The faba bean has the highest CP (6.2%), followed by barley straws (5.5%), vetch haulms (5.5%), Eragrostis tef (3.7%), wheat straws (3.2%), and maize stover (2.9%). In general, all crop residues contain CP content below the critical CP level required even for livestock maintenance. The highest NDF was found in barley straw (75.1%), which was followed by wheat straw (72.0%), Eragrostis tef straw (70.2%), vetch haulms (69.3%), maize stover (67.4%), and faba bean haulms (67.2%). All types of crop residues were classified as low-quality feed because they contained more than 65% NDF, which could affect feed intake and livestock production. Therefore, crop residues must be improved using mechanical, biological, and chemical methods in order to increase livestock production in the study areas by increasing feed consumption.